The association between implementation of multidisciplinary rounds and clinical outcomes - Sreepathy, Pranati; Kim, Yoo Jin; Ahuja, Zaneta; Shroff, Adhir R.; Nazir, Noreen T. (Frontiers in Cardiovascular Medicine, 2022)
Background Multidisciplinary rounds (MDR) consisting of social workers, dietitians, pharmacists, physical therapists, nurses, and physicians have been implemented at many healthcare institutions to address the complex components of inpatient care. However, little is known on the association of MDR on clinical outcomes across cardiovascular pathologies. This study aimed to investigate the impact of MDR on cardiovascular patients. Methods Hospital admissions to inpatient cardiology were evaluated prior to (November 2017 to November 2018) and after implementation of MDR (December 2018 to August 2020) at a metropolitan academic medical center. The following outcomes were evaluated: clinical complications (incidence of stroke, gastrointestinal bleed, myocardial infarction, or systemic infection during hospitalization), Length of Stay (LOS), 30-day readmissions and all-cause in-hospital mortality. Secondary outcomes included utilization of physical therapy and dietary services. Results Admissions were evaluated prior to (N = 1054) and after (N = 1659) MDR implementation. All-cause in-hospital mortality after MDR implementation decreased significantly from 2.8 to 1.6% (P = 0.03). Although the number of complications and LOS decreased, these differences were not statistically significant. No significant change was observed in 30-day readmissions. Significant increase in the utilization of physical therapy (34.2 to 53.5%; P < 0.01) and dietary services (7.2 to 19.3%; P < 0.01) were observed. Conclusion Multidisciplinary rounds implementation was associated with significantly decreased mortality and positively impacted resource utilization with increased consultations for ancillary services. MDR is a high impact intervention that utilizes existing resources to improve mortality and should be implemented especially for cardiovascular patients. Further investigation into the benefit of MDR across different patient populations and care settings is warranted.